Hepatic Effects from Subacute Exposure to Insecticides in Adult Male Wistar Rats - Aldana-Madrid, María-Lourdes; Shibayama, Mineko; Calderon, Margarita; Silva, Angélica; Silveira-Gramont, María-Isabel; Tsutsumi, Víctor; Zuno-Floriano, Fabiola-Gabriela; Rincón-Sánchez, Ana-Rosa (IntechOpen, 2012)
None